2014
DOI: 10.1007/s10295-014-1431-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of a phenotypic assay for characterisation of ethanologenic yeast strain sensitivity to inhibitors released from lignocellulosic feedstocks

Abstract: Inhibitors released by the breakdown of plant cell walls prevent efficient conversion of sugar into ethanol. The aim of this study was to develop a fast and reliable inhibitor sensitivity assay for ethanologenic yeast strains. The assay comprised bespoke 96-well plates containing inhibitors in isolation or combination in a format that was compatible with the Phenotypic Microarray Omnilog reader (Biolog, hayward, CA, USA). A redox reporter within the assay permits analysis of inhibitor sensitivity in aerobic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 61 publications
1
57
0
2
Order By: Relevance
“…According to the types of biomass and pretreatment methods, levels of acetic acid often reach very high in lignocellulosic hydrolysates (Klinke et al, 2004; Nakata et al, 2006; Almeida et al, 2007). Additionally, contamination with lactic acid bacteria and acetic acid bacteria increases the concentration of acetic acid in open fermenters (Beckner et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the types of biomass and pretreatment methods, levels of acetic acid often reach very high in lignocellulosic hydrolysates (Klinke et al, 2004; Nakata et al, 2006; Almeida et al, 2007). Additionally, contamination with lactic acid bacteria and acetic acid bacteria increases the concentration of acetic acid in open fermenters (Beckner et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Since hemicellulose and lignin are highly acetylated, acetic acid is released during the pretreatment of the lignocellulosic biomass prior to bioethanol production and remains in hydrolysates (Palmqvist and Hahn-Hägerdal, 2000; van Maris et al, 2006; Vilela-Moura et al, 2011; Koppram et al, 2014). Although the concentration of acetic acid in the lignocellulosic hydrolysates varies widely according to the types of treatment methods and biomass used, a wide range of acetic acid concentrations (0 – 178 mM) was reported in previous studies (Klinke et al, 2004; Nakata et al, 2006; Almeida et al, 2007). Additionally, acetic acid is easily produced in open fermenters due to contamination by lactic acid bacteria and acetic acid bacteria.…”
Section: Introductionmentioning
confidence: 93%
“…Biofilm biomass of C. albicans cultured in RPMI for 24 h was quantified using the crystal violet assay, as previously described (18). Real-time cellular metabolic activity (respiration) was evaluated using phenotypic microarray (PM) analysis as previously described (19). Briefly, a suspension of C. albicans was adjusted to a transmittance of 62% (ϳ5 ϫ 10 6 cells · ml Ϫ1 ) using a turbidimeter.…”
Section: Methodsmentioning
confidence: 99%
“…Furfural and HMF have been shown to be derived from degradation of sugar molecules when under acid catalysed or high temperature hydrolysis (Taherzadeh and Karimi, 2008). Previous studies have demonstrated that 20 mM furfural inhibits S. cerevisiae (Park et al, 2011;Greetham et al, 2014). This would suggest that the concentrations detected in these hydrolysates would not be significantly problematic for S. cerevisiae.…”
Section: Metabolic Profiling Of Yeast Cultured In Pre-treatment Genermentioning
confidence: 99%